The Use of Android-Based Applications “Drinking Alert” to Influences on Knowledge and Attitude of Adolescents in Fulfillment Mineral Water Consumption in Bengkulu City - Wisuda Andeka Marleni; Ratu Matahari; Lisma Ningsih; Reka Lagora Marsofely (Universitas Airlangga, 2023)
Humans need source of energy, one of them is the need for drinking water. It is known that 70% of the parts in the human body are liquid. Humans need an adequate supply of water to maintain freshness and physical fitness. A study in Indonesia found that 49.5% of adolescents and 42.5% of adults were mildly dehydrated. Teenagers are more often dehydrated because of the many physical activities of adolescents that can drain energy and body fluids, causing a lack of fluid consumption. The purpose of the study was to determine the effect of the use of an android-based application drinking alert on the knowledge and attitudes of adolescents in fulfillment water consumption in Bengkulu City. This study was quantitative with the quasi-experimental design. There were 60 respondents that chosen by purposive sampling method in the intervention group dan control group with inclusion are adolescencts aged 12-14 years, and adolescents who can be invited to communicate and have an android device and distinguish the exclusion of adolescents who experience impaired kidney function and do not want to be involved in research. There were 60 respondents who were engaged to this study. The data was analyzed using Wilcoxon and Mann-Whithney test. Based on the results of the study there is difference on the knowledge and attitude scores of adolescents given an android-based application using drinking Alert and control cards with (p < 0.05). The use of the android-based application